Exploring Official Certifications for Romance Minority Languages in the European Context - Antony Hoyte-West (Linguaculture)
This article presents a brief overview of the official language certifications available for seven Romance minority languages which are spoken in Europe: Aragonese, Asturian, Catalan, and Galician (primarily spoken on the Iberian peninsula), Corsican and Occitan (spoken in France), and Romansh (spoken in Switzerland). As a component of a broader project which has previously examined official credentials for selected Celtic and Slavic languages, the study first outlines general information about the Romance language family and the minority and minoritised languages which are members of it, before giving a short overview of language certifications as well as the study’s methodology and research questions. Subsequently, in adopting a similar approach to the previous analyses, each of the seven linguistic case studies is presented with the objective of obtaining core information about the types, levels, awarding institutions, and wider recognition relating to the certifications concerned. These findings are then discussed, after which some conclusions and additional research possibilities are offered.